Disability resources in higher education, part 1: Budget and finance fundamentals. Issue 6 (22nd January 2018) - Thompson, Tom L.
Abstract : If you listen carefully, you can hear groans and sounds of exasperation coming from provost or chief student affairs officer offices! Why? They have just received news from their Disability Resources and Services Office that $25, 000 is needed for a book to be produced in Braille, or that a deaf medical student's interpreting and captioning is estimated to cost $40, 000.